2010
DOI: 10.1002/jccs.201000098
|View full text |Cite
|
Sign up to set email alerts
|

Application of Multi‐walled Carbon Nanotube Modified Carbon Ionic Liquid Electrode for the Voltammetric Detection of Dopamine

Abstract: In this paper a carbon ionic liquid electrode (CILE) was fabricated by using ionic liquid 1‐butyl‐3‐methylimidazolium hexafluorophosphate (BMIMPF6) as the binder. Then a Nafion and multi‐walled carbon nanotubes (MWCNTs) composite material was further cast on the CILE surface to get a modified electrode denoted as Nafion‐MWCNTs/CILE. The fabricated electrode showed strong electrocatalytic ability to the oxidation of dopamine (DA) with a pair of well‐defined redox peaks appeared. Compared with other electrodes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…where n is the number of electrons transferred, F is the Faraday constant, A is the surface area of the electrode, D is the diffusion coefficient, C is the bulk concentration of the species, t is the potential pulse width, Q c is the capacitive or double layer charge and Q ads is the faradaic component due to the oxidation of adsorbed species .…”
Section: Resultsmentioning
confidence: 99%
“…where n is the number of electrons transferred, F is the Faraday constant, A is the surface area of the electrode, D is the diffusion coefficient, C is the bulk concentration of the species, t is the potential pulse width, Q c is the capacitive or double layer charge and Q ads is the faradaic component due to the oxidation of adsorbed species .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the detection limits (at a signal-to-noise ratio of 3) were measured to be 0.88, 068, 0.24, and 0.11 μM, respectively. It is worth noting that the exceptional detection limit of the graphene/EMI–SCN electrode is superior to most values reported in the literature (see Table S1).…”
Section: Resultsmentioning
confidence: 62%
“…Some previous works utilized graphene/IL composite electrodes for the sensing of hydroquinone, ascorbic acid (AA), dopamine (DA), uric acid (UA), and DNA. , Many studies have found that IL incorporation enhances electrode-sensing performance. A short review of previous works in this field is provided in the Supporting Information (see Table S1). …”
Section: Introductionmentioning
confidence: 99%
“…A plot of logj pa vs logv (result not shown) was used to determine whether the oxidative behavior of CAF was due to diffusion or adsorption. The slope of 0.87 > 0.5 for a theoretical diffusion-controlled process allowed to conclude that a mixed behavior showing both adsorption and diffusion-controlled processes were involved [36]. When the scan rate increased, the anodic peak po-…”
Section: Effect Of Scan Ratementioning
confidence: 89%